Bidirectional juxtacrine ephrinB2/Ephs signaling promotes angiogenesis of ECs and maintains self-renewal of MSCs. (July 2018) - Cao, Cen; Huang, Ying; Tang, Qingming; Zhang, Chenguang; Shi, Lei; Zhao, Jiajia; Hu, Li; Hu, Zhewen; Liu, Yun; Chen, Lili
Abstract: Co-transplantation of endothelial cells (ECs) and mesenchymal stem cells (MSCs) is an important strategy for repairing complex and large bone defects. However, the ways in which ECs and MSCs interact remain to be fully clarified. We found that forward ephrinB2/Ephs signaling from hBMSCs to hUVECs promoted the tube formation of hUVECs by activating the PI3K/AKT/mTOR pathway. Reverse ephrinB2/Ephs signaling from hUVECs to hBMSCs promoted the proliferation and maintenance of hBMSCs self-renewal via upregulation of OCT4, SOX2, and YAP1. Subcutaneous co-transplantation of ECs and MSCs in nude mice confirmed that forward ephrinB2/Ephs signaling could increase the cross-sectional area of blood vessels in the transplanted area, and reverse ephrinB2/Ephs signaling could maintain the self-renewal of transplanted hBMSCs in vivo . Based on these results, ephrinB2/Ephs bidirectional juxtacrine regulation between ECs and MSCs plays a pivotal role in improving the healing of bone defects by promoting angiogenesis and achieving a sufficient number of MSCs. Graphical abstract: Highlights: hBMSCs promote hUVECs angiogenesis through forward ephrinB2/Ephs signaling. hUVECs maintain self-renewal of hBMSCs through reverse ephrinB2/Ephs signaling. EphrinB2/Ephs signaling is important for hBMSCs/hUVECs co-transplantation.